Tactics of Surgical Treatment of Postinfarction Ventricular Septum Rupture Depending on the Time after the Development of an Acute Myocardial Infarction - Aliyev, Ramil A.; Lebedieva, Yelizaveta O.; Grusha, Mykhailo M.; Brianskyi, Mykyta M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The article is dedicated to topical issues of the tactics of surgical treatment of postinfarction ventricular septum rupture (PIVSR). Based on the study of the peculiarities of surgical treatment of ventricular septal defect in patients with different deadlines for surgical intervention after the development of acute myocardial infarction (AMI), the most appropriate approach to the correction of PIVSR in such patients was determined. In particular, taking into account mortality risk (42 %), the most reasonable is the use of wait-and-see tactics in the management of patients with PIVSR at the early stages after the development of AMI. At the same time, the decision on the timing of surgical intervention should be made individually, taking into account the clinical condition of the patient and the course of the postinfarction heart remodeling. Special attention is paid to the analysis of the effectiveness of the use of intra-aortic balloon counterpulsation and the time intervals of surgical intervention from the moment of hospitalization in patients with PIVSR. It was found that clinical course of coronary heart disease complicated by PIVSR can be extremely unpredictable not only in the early postinfarction period, but also up to 2 months after the development of AMI. In addition, when planning the amount of surgical intervention, it is necessary to take into account the presence of multivessel atherosclerotic lesions of the coronary arteries in patients with PIVSR, regardless of the timing after the development of AMI.